Transformative doctoral research practices for professionals - Burnard, Pamela; Dragovic, Tatjana; Flutter, Julia; Alderton, Julie (Critical issues in the future of learning and teaching ;, 2016)
The purpose and impact of the professional doctorate - or EdD (Doctor of Education) - has long been debated. What should it be? Who should do it? Why is it worth doing? How should it be taught? What makes the EdD distinctive, unique and worthwhile? Internationally, at the level of program development and provision, universities are increasing the range of transformative professional doctorate practices while recruiting larger numbers of students from a wider range of professions. Transformative Doctoral Research Practices for Professionals offers unique insight into the teaching, learning, thinking and doing of doctoral education. In the form of a collaboratively authored volume this book offers the first institutional-specific collection that focuses on doctoral research practices. It showcases: the practices of researching professionals at different phases and stages of a five year doctoral journey; the imperative of reflexivity as one moves from practitioner to researching professional and scholar; and the placing of 'practice' at the centre of a doctoral program specifically designed for professionals. This book shares the lived-through debates, deliberations, challenges and experiences of a group of professional (practitioner) doctoral students, their supervisors and lecturers. The critical perspectives and examples explored offer a wealth of insights on the distinct practices and unique journeying of professional practitioners embarking on professional doctorates. This volume invites you to reflect on and enter into dialogue with your peers and professional learning and research communities about the distinctiveness of the professional doctorate.